Structural elucidation of Eucalyptus lignin and its dynamic changes in the cell walls during an integrated process of ionic liquids and successive alkali treatments. (December 2016) - Li, Han-Yin; Wang, Chen-Zhou; Chen, Xue; Cao, Xue-Fei; Sun, Shao-Ni; Sun, Run-Cang
Highlights: ILs combined with successive alkali treatments were performed to isolate lignin. ILs pretreatment increased the extraction of the alkali-soluble lignin. The integrated treatment tended to generate S-rich lignin macromolecules. The delignification process in the Eucalyptus cell walls was monitored visually. Lignin dissolved was mainly stemmed from the secondary wall regions. Abstract: An integrated process based on ionic liquids ([Bmim]Cl and [Bmim]OAc) pretreatment and successive alkali post-treatments (0.5, 2.0, and 4.0% NaOH at 90 °C for 2 h) was performed to isolate lignins from Eucalyptus . The structural features and spatial distribution of lignin in the Eucalyptus cell wall were investigated thoroughly. Results revealed that the ionic liquids pretreatment promoted the isolation of alkaline lignin from the pretreated samples without obvious structural changes. Additionally, the integrated process resulted in syringyl-rich lignin macromolecules with more β - O -4′ linkages and less phenolic hydroxyl groups. Confocal Raman microscopy analysis showed that the dissolution behavior of lignin was varied in the morphologically distinct regions during the successive alkali treatments, and lignin dissolved was mainly stemmed from the secondary wall regions. These results provided some useful information for understanding the mechanisms of delignification during the integrated process and enhancing the potential utilizations of lignin in future biorefineries.